Updates in the situation under electronic surveillance in accordance with Law No. 24-06 amending and supplementing Decree No. 66-156, which includes the Algerian Penal Code - Lina, Bouzitouna (The International tax journal, 2025)
No one denies that, in keeping pace with scientific developments in the field of modern technology, the idea of ​​using technology to modernize and rationalize the penal system has emerged. This is a necessary response resulting from the worsening negative effects of short-term imprisonment, on the one hand, and to alleviate the pressure on penal institutions, on the other. The search for modern penal methods as an alternative to short-term imprisonment has become a necessity, and this is what the Algerian legislator has sought to achieve by introducing electronic monitoring pursuant to Law No. 24-06 amending and supplementing the Penal Code. This law aims to strike a balance between society's interest in deterrence and the convict's interest in protecting their rights and freedoms.